Deadbeat predictive direct power control of interleaved buck converter-based fast battery chargers for electric vehicles - Choi, Hye Won; Kim, Seok Min; Kim, Jinwoo; Cho, Younghoon; Lee, Kyo Beum (Journal of Power Electronics, 2020)
This paper presents a deadbeat predictive direct power control (DB-DPC) scheme for a fast battery charger to improve its dynamic performance and stability. Recently, battery chargers have been adopting paralleled multi-leg converters based on silicon carbide (SiC) devices to increase power capacity, which reduces the charging duration. However, the inherent instability of the battery is regarded as a crucial issue during the fast charging process. Therefore, the proposed DB-DPC provides a stable steady state since it includes real-time estimation of the variable battery impedance. Furthermore, the DB-DPC effectively minimizes the rising and settling time, which demonstrates fast-dynamic response characteristics when compared to proportional–integral (PI) control. The control performance is verified by various simulation and experimental results.
Keywords: Control performance; Dynamic performance; Fast dynamic response; Inherent instability; Interleaved buck converters; Predictive direct power controls; Real-time estimation; Silicon carbides (SiC); Deadbeat predictive control; Direct power control; Electric vehicle charger; Fast power tracking control; Multi-leg interleaved converter